Implementation of Parallel Collection Equi-Join Using MPI - Lee, Nung Kion (Springer Berlin Heidelberg, 2002)
One of the collection joins types in Object Oriented Database (OODB) is collection equi-join. The main feature of collection joins is that they involve collection types. In this paper we present our experience in implementing collection equi-join algorithms by using Message Passing Interface (MPI). In particular, it layouts the fundamental techniques that are used in the implementation and that may be applicable to other collection joins. Two collection equi-joins discussed here are Double Sortmerge and Sort Hash Join. The implementation was done on a clustered environment and employed a data parallelism concept.